Implementasi Bimbingan Penyuluh Agama terhadap Narapidana di Rumah Tahanan Kelas II B Singkil - Wulandari Rahmadana; Zulkarnain Abdurrahman (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Being in prison is a new chapter in the life of a convict. As a result of his actions, his life was restrained and he had to be separated from the people he loved. Under these conditions, religious guidance is needed so that they remain strong and not stressed in facing life's trials. This study aims to determine the methods of implementing the guidance of religious instructors for prisoners in the Singkil Class II-B Detention Center, the inhibiting factors for the implementation of guidance and the effectiveness of implementing the guidance of religious instructors for prisoners. This research is a type of qualitative research with a descriptive approach. The subjects of this study involved 2 religious educators, 4 convicts, and 1 prison officer. Data collection techniques using observation, interviews and documentation. The results of this study indicate that the presence of Islamic religious instructors at the Aceh Singkil Ministry of Religion has a very significant role in guidance or coaching efforts at the detention center because until now the detention center has not had an internal counselor. The guidance method of the religious instructor implemented in the detention center is a method of direct communication in the form of religious lectures and guidance on reading the Koran. Obstacles in the implementation of guidance are very diverse, some are related to extension workers, convicts, detention centers and the coaching system. This is marked by an increase in convicts' understanding of Islamic teachings and their better behavior.